2014
DOI: 10.1136/archdischild-2013-304793
|View full text |Cite
|
Sign up to set email alerts
|

Does failed chronic wet cough response to antibiotics predict bronchiectasis?

Abstract: Further investigations including a MDCT scan should be considered in a child with a chronic wet cough that persists following 4 weeks of oral antibiotics. However, while reducing the likelihood of underlying bronchiectasis, responding well to a single prolonged course of antibiotics does not exclude this diagnosis completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 31 publications
(34 reference statements)
1
53
0
Order By: Relevance
“…aureus) found in the lower airways of children with chronic wet or productive cough were associated with increased likelihood of cough resolution [16,48,52]. However, symptomatic recurrences were common [16,48,52], occurring in as many as 76% of cases, while a poor response to ⩾4 weeks of treatment increased the likelihood of the presence of underlying bronchiectasis [47].…”
Section: Therapy (Kq6)mentioning
confidence: 98%
See 2 more Smart Citations
“…aureus) found in the lower airways of children with chronic wet or productive cough were associated with increased likelihood of cough resolution [16,48,52]. However, symptomatic recurrences were common [16,48,52], occurring in as many as 76% of cases, while a poor response to ⩾4 weeks of treatment increased the likelihood of the presence of underlying bronchiectasis [47].…”
Section: Therapy (Kq6)mentioning
confidence: 98%
“…Data suggest that children should be referred for further investigations when specific cough pointers (box 2) are present or when the wet cough does not respond to 4 weeks of antibiotics. One study found that failure of the cough to respond to 4 weeks of antibiotics increased the chance of bronchiectasis being present (adjusted OR 20.9, 95% CI 5.4-81.8) [47]. Another study reported that the duration of chronic wet cough was significantly associated with increased risk of structural airway abnormalities and increased Bhalla scores on chest computed tomography (CT) scans [46].…”
Section: Other Causes Of Chronic Wet Cough In Children (Kq2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients are not well after treatment lasting less than two weeks, or quickly relapse (1,18). Therefore, treatment for 4 -6 weeks used to be recommended (10,19). Our experience tallies with the literature -antibiotic treatment is highly efficacious for some children who become symptom-free after a few days, while others get better gradually over a period of 2 -4 weeks (8).…”
Section: Treatmentmentioning
confidence: 69%
“…When protracted bacterial bronchitis is suspected and antibiotics are ineffective, the child should be assessed for other possible causes (19), and other severe pulmonary disease must also be considered if Pseudomonas aeruginosa develops in the bacterial culture. Further assessment is also recommended in the event of a second recurrence of symptoms (1,2).…”
Section: Differential Diagnosesmentioning
confidence: 99%